What Happens when Companies (don't) Do What they Said they would? Stock Market Reactions to Strategic Integrity. Issue 3 (15th April 2018) - Mavis, Christos P.; Richter, Ansgar; Landau, Christian; Schmidt, Sascha L.; Simons, Tony; Steinbock, Kai
Abstract : Literature on the 'power of words' has emphasized the importance of a firm's corporate communication as a source of legitimacy and reputation in the eyes of its stakeholders. We argue that it is not just the content or style of a firm's communication about its strategy, but also the alignment between this communication and its subsequent strategic actions that help build legitimacy among stakeholders and creating firm performance. We introduce the organization‐level construct of 'strategic integrity' to capture the notion of alignment between a firm's strategy communication and its subsequent strategic actions. We investigate the importance of strategic integrity using the case of the German pharmaceuticals firm Bayer AG in the context of its portfolio restructuring. The results of an event study of 80 acquisitions/divestments indicate that stock markets react positively to strategic integrity.